(NkETSKIJ SBORNIK (B/s - (NiWANOW(B, (NwSEWOLOD wQ^ESLAWOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NWOST(B. (NLIT(B.,s, 1969)
(NbIBLOGR(B. (NPO KETSKOMU QZ(B., (NSOST(B. (Nw(B.(Nn(B. (NtOPOROW(B, (NS(B. 243-283s
(NwYP(B. 2 (1969; 291 (NS(B.) :s (NmIFOLOGIQ(B, (N\TNOGRAFIQ(B, (NTEKSTYs
(NiN(B-(NT WOST(B. (NQZ(B. (NmOSKWAs
Keywords: (NkETSKIJ FOLXKLORs; (NkETSKIJ QZYKs; (NkETY (B- (N|TNOGRAFIQs